The Relationship between Theme and Character in Fiction Movie Inside Out - Feriyanti Elina Gultom (BAHAS, 2022)
AbstractTheme is the main idea or thought in writing. Meanwhile character is the actor who experiences events and problems in the story or fiction so that the event become an interesting story. There is a close relationship between theme and character in story.The purpose of this study is to describe: (1) the relationship between theme and character through feelings, (2) the relationship between theme and character through thoughts, and (3) the relationship between theme and character through action. This study used a qualitative approach. The method used is descriptive analysis. Types of data were in the form of sentences, phrases, and paragraphs related to the character's feelings, character's thoughts, and character's actions. Inside Out is an American animated film produced by Disney Pixar about emotional instability of 11 year old girl. Conclusion, in this study, the theme that is influenced by feelings is dominated by the egoic theme. The theme which is influenced by the most dominating thought is the physical theme, and the theme which is influenced by action is dominated by organic theme.Keywords: Relationship of Theme, Character, Fiction